Energy and exergy performance improvement of coupled PV-TEG module by using different shaped nano-enhanced cooling channels - Selimefendigil, Fatih; Okulu, Damla; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2024)
In this study, impacts of using different cooling channels (L, T and U-shaped) on the energy and exergy performances of combined PV/TEG (photovoltaic/thermoelectric generator) unit are numerically assessed by using FEM based three dimensional high fidelity computational simulations. Cooling performance is boosted by using ternary nanofluid in the channels. The study is conducted for a range of Reynolds numbers (Re, between 50 and 500), nanofluid cooling inlet temperatures (between 15 degrees C and 23 degrees C), and nanoparticle loading amounts (between 0 and 3%). Evaluations are done on average PV-cell temperature, PV/TEG output powers, exergy efficiency, improve potential (IP), and sustainability index (SI). U-shaped and T-shaped channels are found to offer the greatest and worst cooling performances among various cooling channels. When comparing the lowest and maximum Re cases, the average temperature drops for PV cells are 3.54 degrees C for T channel and 2.55 degrees C for U channel. Exergy efficiency is determined to be 14.2% with T-channel at Re=50 and 14.6% with U-channel at Re=500. Taking into consideration different channels, an increase in the inlet temperature from 15 degrees C to 23 degrees C leads to an average rise in cell temperature of 6 degrees C. The IP rises with coolant inlet temperature while using T-channel. SI values fall as input temperature increases, although values between 1.164 and 1.175 may be achieved by using different cooling channels. Using nanofluid with higher loading results in higher exergy efficiency when comparing exergetic performances, with U-channel design exhibiting the highest performance. For the range of parameters considered, the coolant inlet temperature at the channel entry has the highest effect on PV cell temperature reduction; 8.5 degrees C of temperature reduction is feasible. By employing U-channel cooling, the maximum value of Re, the highest loading of nanoparticles, and the lowest inlet temperature yield the best exergy efficiency. The best and worst situations' respective exergy efficiencies are determined to be 15% and 14.1%. Utilizing T-channel cooling with water at a flow flow rate and a higher input temperature is the scenario with the biggest potential for exergy improvement; the value is 2.9. When different operational parameters are varied, the SI falls between 1.176 to 1.16.
Keywords: PV-TEG combined unit; Ternary nanofluid; L/U/T channel; Exergy; CFD; Sustainability